Pengembangan Alat Peraga Matematika Berbasis Metode Montessori pada Papan Perkalian di Kelas II MI - Jazila Adelina Lubis; Andina Halimsyah Rambe (EduInovasi: Journal of Basic Educational Studies, 2023)
This study aims to determine the feasibility and effectiveness of teaching aids and to develop multiplication board aids based on Montessori in order to improve the ability to calculate multiplication and create a more interesting and enjoyable learning process for class II MIN 12 students in Medan City. This study uses the Research and Development (R&D) method using research and development procedures from Borg and Gall with 8 steps out of 10 steps namely: research and data collection, planning, product draft development, initial field trials, product revisions, field trials main, operational test and final product revision. Data collection techniques with observation, interviews, questionnaires and tests. Data analysis techniques using quantitative descriptive statistics. From the results of validation by material experts, media experts and field trials conducted by teachers and students it can be seen that they fall into the very feasible category. This is indicated by an increase in student learning outcomes of 58,6%. The results of field trials also found that visual aids had cognitive and affective impacts in the form of increasing students' concentration and interest in learning. Keywords: development, props, multiplication board, montessori